1986
DOI: 10.1002/qua.560290545
|View full text |Cite
|
Sign up to set email alerts
|

The theoretical approach to surface chemistry and heterogeneous catalysis

Abstract: Transition metals are the most interesting items among heavy atoms due to their extensive use in catalysis. Present understanding of heterogeneous catalytic reactions is still very poor, and new experimental and theoretical techniques have been developed in recent years with the aim of elucidating the mechanism of adsorption and reaction of simple molecules over metal surfaces or clusters. Empirical, semiempirical, and ab initio methods of calculations are briefly reviewed: results and perspectives are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…One of the most popular semiempirical methods utilized for studying different processes on metal surfaces is the extended Huckel method. This method was originally designed for organic compounds, and it was later parametrized for transition metals in a way that also partially accounts for relativistic effects. However, in our preliminary studies, we have found that the convergence of such calculations for certain d -metals (including gold) was very problematic.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most popular semiempirical methods utilized for studying different processes on metal surfaces is the extended Huckel method. This method was originally designed for organic compounds, and it was later parametrized for transition metals in a way that also partially accounts for relativistic effects. However, in our preliminary studies, we have found that the convergence of such calculations for certain d -metals (including gold) was very problematic.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…It suggested to us to try another recently developed semiempirical method, parametrized for most elements in the periodic table, including transition metals, namely, the PM6 model . In addition, unlike the very approximate construction of the (extended) Huckel method, ,, the PM6 method is based on less dramatic approximations, which gives it more flexibility for a better description of many systems.…”
Section: Theoretical Modelmentioning
confidence: 99%